2020
DOI: 10.2147/idr.s253540
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Features, Laboratory Characteristics and Prognostic Factors of Severity in Patients with Rickettsiaceae at Two Military Hospitals, Northern Vietnam</p>

Abstract: Introduction: Rickettsioses are diseases caused by intracellular Gram-negative bacteria of the Rickettsiaceae family and transmitted through the bite of infected ticks or mites. Aim of Study: To investigate the clinical and subclinical characteristics and prognostic severe factors of the disease caused by Rickettsiaceae. Methods: A prospective, descriptive cross-sectional study was conducted at Department of Infectious Diseases of two military hospitals in Northern Vietnam from May 2013 to June 2019, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
0
2
0
4
Order By: Relevance
“…In this case, IFA, the gold standard diagnostic test, was used to detect IgM antibodies specific to the MSF infection. The patient’s laboratory results indicated thrombocytopenia, elevated liver enzyme levels, and hemoglobin levels, which are common abnormalities observed in MSF patients [ 14 ]. In the early stages of MSF, serological tests are not reliable for diagnosis because of the delayed development of antibodies against R. conorii .…”
Section: Discussionmentioning
confidence: 99%
“…In this case, IFA, the gold standard diagnostic test, was used to detect IgM antibodies specific to the MSF infection. The patient’s laboratory results indicated thrombocytopenia, elevated liver enzyme levels, and hemoglobin levels, which are common abnormalities observed in MSF patients [ 14 ]. In the early stages of MSF, serological tests are not reliable for diagnosis because of the delayed development of antibodies against R. conorii .…”
Section: Discussionmentioning
confidence: 99%
“…Lâm sàng sốt mò rất đa dạng, từ nhiễm trùng không triệu chứng đến bệnh cảnh nặng, có khả năng tử vong. Tỷ lệ tử vong do sốt mò dao động khoảng 1 -6% tương tự như ở Thái Lan và các nước châu Á 7,9,12 . Trong khi sốt biểu hiện gần như ở tất cả bệnh nhân, vết loét (eschar) là dấu hiệu có giá trị gợi ý chẩn đoán tốt chỉ gặp khoảng một nửa đến ba phần tư số bệnh nhân (dao động từ 47,4 -76%), sưng hạch gặp ở khoảng 1/4 đến 2/3 số bệnh nhân (dao động từ 23,4 -64,1), còn phát ban trên da (rash) chỉ phát hiện ở khoảng 1/3 (dao động từ 5,3 -37,7%) [7][8][9][10]12 .…”
Section: Sốt Mò (Scrub Typhus)unclassified
“…Tỷ lệ tử vong do sốt mò dao động khoảng 1 -6% tương tự như ở Thái Lan và các nước châu Á 7,9,12 . Trong khi sốt biểu hiện gần như ở tất cả bệnh nhân, vết loét (eschar) là dấu hiệu có giá trị gợi ý chẩn đoán tốt chỉ gặp khoảng một nửa đến ba phần tư số bệnh nhân (dao động từ 47,4 -76%), sưng hạch gặp ở khoảng 1/4 đến 2/3 số bệnh nhân (dao động từ 23,4 -64,1), còn phát ban trên da (rash) chỉ phát hiện ở khoảng 1/3 (dao động từ 5,3 -37,7%) [7][8][9][10]12 . Vị trí vết loét có thể ở bất kỳ bộ phận nào trên cơ thể, nhưng xu thế ở các vùng da mỏng, nếp gấp, kín đáo nên có thể ít được chú ý, tương tự dấu hiệu phát ban trên da ở những bệnh nhân có màu da sậm cũng dễ bị bỏ qua.…”
Section: Sốt Mò (Scrub Typhus)unclassified
See 1 more Smart Citation
“…Clinical signs and symptoms of scrub typhus are fever, headache, myalgia, cough, and gastrointestinal symptoms, with or without escharation [ 19 ]. A recent study from northern Vietnam reported that 70% of patients with scrub typhus had eschars, 60% had skin-conjunctiva congestion, and 44% had lymphadenopathy [ 20 ]. Untreated acute scrub typhus cases have a high risk of developing severe manifestations, including microangiopathy, septic shock, acute respiratory failure, congestive heart failure, severe jaundice, or acute renal failure [ 19 ].…”
Section: Introductionmentioning
confidence: 99%